Central Bank Digital Currency E-Rupee (e`) Usage Patterns : The Interplay of Awareness and Satisfaction in India - Nayak, Daravath Vikas; Kumar, A. Arun (Indian Journal of Finance, 2025)
Purpose : The present study assessed bank employees’ usage patterns, degree of awareness, and satisfaction level with the Central Bank Digital Currency. Various features such as accessibility, transparency, security, and efficiency were used to analyze bank employees’ perceptions of the digital currency ecosystem. Design/Methodology : The regression analysis, factor analysis of variance, t-test, and descriptive analysis were used to evaluate the relationship between awareness, adoption, satisfaction, and usability of Indian e-rupee (e`) digital currency. To gain a deeper understanding of the effectiveness of the Central Bank Digital Currency (e`) currently implemented in India, a study was conducted involving a selected sample of 202 bank employees. Findings : In the current study, a model has been conceptualized to test the potency of e` among bank employees in Indian banks. The trends and findings provided valuable insights to experts and practitioners in the context of e` digital currency usage. Practical Implications : This study is a ground-breaking analysis of bank employees’ opinions on digital money and their preferences for transactions with it. It also analyzed the impact of Central Bank Digital Currency usage and the factors determining its usability. Originality : This study is a novel contribution focusing on awareness and satisfaction in India. It could be assessed based on its unique contribution to the existing literature and understanding of emerging technology.